An examination of food neophobia in older adults. (March 2019) - Soucier, Victoria D.; Doma, Katarina M.; Farrell, Emily L.; Leith-Bailey, Erin R.; Duncan, Alison M.
Highlights: Food neophobia can be a contributing factor to nutritional risk in older adults. Average food neophobia score was moderate in a sample of 250 older adults. Food neophobia was not related to older adult health-related variables. Abstract: Older adults are the fastest growing demographic worldwide and are also at increased nutritional risk. Food neophobia, the reluctance to eat and/or avoidance of novel foods, can be a contributing factor to nutritional risk and research in older adults is limited. The purpose of this study was to examine food neophobia and attitudes toward new foods in a sample of older adults. A total of 250 community-dwelling older adults (≥65 years) were recruited to complete a researcher-administered questionnaire that explored attitudes towards new foods and food neophobia, which was assessed using the 10-question Food Neophobia Scale. Cronbach's alpha for the Food Neophobia Scale was 0.82, indicating a high degree of internal validity. Food neophobia scores were normally distributed with a mean ± SE of 29.6 ± 0.70. Participants were divided into three groups based on their food neophobia score: low (10–23; n = 81), medium (24–33; n = 88) and high (34–67; n = 81). Participants with a high degree of food neophobia were less willing to try new foods or food products (p < 0.0001). Participant demographic (age, sex, ethnicity, education, annual household income) and health (number of prescription medications and diagnosed health conditions) characteristics did not significantly differ among food neophobia groups. This data adds to the limited literature on food neophobia in older adults and supports the need for further investigation into potential determinants of food neophobia.